2012
DOI: 10.1104/pp.112.204578
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of a Silicon Transporter Gene Implicated in Silicon Distribution in Barley    

Abstract: Silicon (Si) is a beneficial element for plant growth. In barley (Hordeum vulgare), Si uptake by the roots is mainly mediated by a Si channel, Low Silicon1 (HvLsi1), and an efflux transporter, HvLsi2. However, transporters involved in the distribution of Si in the shoots have not been identified. Here, we report the functional characterization of a homolog of HvLsi1, HvLsi6. HvLsi6 showed permeability for Si and localized to the plasma membrane. At the vegetative growth stage, HvLsi6 was expressed in both the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
85
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(92 citation statements)
references
References 28 publications
(36 reference statements)
7
85
0
Order By: Relevance
“…Similar findings were observed in wild and cultivated rice (Mitani-Ueno et al 2013). In addition to rice, similar Si transporters were found in other grasses such as maize, barley and wheat (Mitani et al 2009a, b;Chiba et al 2009;Montpetit et al 2012;Yamaji et al 2012).…”
Section: Introductionsupporting
confidence: 73%
“…Similar findings were observed in wild and cultivated rice (Mitani-Ueno et al 2013). In addition to rice, similar Si transporters were found in other grasses such as maize, barley and wheat (Mitani et al 2009a, b;Chiba et al 2009;Montpetit et al 2012;Yamaji et al 2012).…”
Section: Introductionsupporting
confidence: 73%
“…Recent study in barley (Hordeum vulgare) showed that a silicon transporter HvLsi6 is localized to the plasma membrane at parenchyma cells of vascular bundles and (during reproductive stage) in nodes. This data obtained by Yamaji et al (2012) suggested a role of HvLsi6 in Si xylem unloading in leaf blade and sheath along with intervascular transfer of Si in nodes. Considering homologous transporter OsLsi2 has a similarity level of 82 % in amino acids sequence and is able to mediate efflux of As, HvLsi6 might play a role in xylem unloading of As(III) in graminaceous plants (Ma 2009;Yamaji et al 2012).…”
Section: Transport Of Non-essential Metalsmentioning
confidence: 77%
“…This data obtained by Yamaji et al (2012) suggested a role of HvLsi6 in Si xylem unloading in leaf blade and sheath along with intervascular transfer of Si in nodes. Considering homologous transporter OsLsi2 has a similarity level of 82 % in amino acids sequence and is able to mediate efflux of As, HvLsi6 might play a role in xylem unloading of As(III) in graminaceous plants (Ma 2009;Yamaji et al 2012). transporters and channels in planta (including: ZIP family, Nramp family, LCT1 channels) (Gallego et al 2012).…”
Section: Transport Of Non-essential Metalsmentioning
confidence: 77%
“…Recently, identification of mineral nutrient transporters in node and physiological studies shed a new light on the importance of node for preferential distribution of mineral nutrients to developing and reproductive organs (2,14,(18)(19)(20)(21)(22)(23). The xylem flow in EVBs and DVBs, which are connected by nodal vascular anastomosis (NVA) at the base of the node, are simply divided following the transpiration rate of each upper organ.…”
Section: Discussionmentioning
confidence: 99%